T cells in ARAP-deficient mice present defective T cell receptor signaling and reduced severity in an experimentally-induced autoimmune disease - Jee-Hae Kim; Seung Hee Jung; Chohee Park; Jong Ran Lee (Frontiers in Immunology)
We previously reported a novel adaptor protein, ARAP, required for T cell receptor signaling and integrin-mediated adhesion. The present study investigates further the role of ARAP in T cell biology using mice with an ARAP gene deficiency. Similar to wild-type mice, ARAP-deficient mice participate in normal breeding and immune cell development. Similar defects were observed in the T cell receptor signaling and adhesion of ARAP-deficient mice, as shown in previous studies investigating ARAP-suppressed Jurkat T cells. ARAP deficiencies analyzed in vivo presented a less severe clinical course of experimental autoimmune encephalomyelitis (EAE) following immunization of mice with the myelin oligodendrocyte glycoprotein (MOG). Serum levels of MOG-specific antibodies and IFN-γ were also reduced in ARAP-deficient EAE mice compared to wild-type EAE mice. Moreover, adoptive transfer of ARAP-deficient T cells induced less severe EAE in recombination-activating gene 1-deficient mice than wild-type T cell transfer. These results strongly suggest that ARAP positively regulates T cell function, while ARAP deficiency in T cells reduces the severity and incidence of EAE.